2022
DOI: 10.1001/jama.2022.9009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bariatric Surgery With Cancer Risk and Mortality in Adults With Obesity

Abstract: IMPORTANCE Obesity increases the incidence and mortality from some types of cancer, but it remains uncertain whether intentional weight loss can decrease this risk.OBJECTIVE To investigate whether bariatric surgery is associated with lower cancer risk and mortality in patients with obesity. DESIGN, SETTING, AND PARTICIPANTSIn the SPLENDID (Surgical Procedures and Long-term Effectiveness in Neoplastic Disease Incidence and Death) matched cohort study, adult patients with a body mass index of 35 or greater who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(149 citation statements)
references
References 36 publications
1
108
0
6
Order By: Relevance
“…Important retrospective work has shown that patients who underwent bariatric surgery had reduced risk of both pre-menopausal and post-menopausal breast cancer with a 64% reduced risk in pre-menopausal ER-tumors, typically the most aggressive tumors with the worst outcomes ( Feigelson et al, 2020 ). Furthermore, reduced recurrence and mortality from cancer have been observed in bariatric surgery patients ( Aminian et al, 2022 ; Bruno and Berger, 2020 ; Zhang et al, 2020a ) although underlying mechanisms remain unclear. A major question remains regarding whether reductions in cancer risk and outcomes are associated with weight loss per se or are due to bariatric surgery-specific benefits, which are inherently challenging to delineate in patients ( Schauer et al, 2017 ; Alvarez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Important retrospective work has shown that patients who underwent bariatric surgery had reduced risk of both pre-menopausal and post-menopausal breast cancer with a 64% reduced risk in pre-menopausal ER-tumors, typically the most aggressive tumors with the worst outcomes ( Feigelson et al, 2020 ). Furthermore, reduced recurrence and mortality from cancer have been observed in bariatric surgery patients ( Aminian et al, 2022 ; Bruno and Berger, 2020 ; Zhang et al, 2020a ) although underlying mechanisms remain unclear. A major question remains regarding whether reductions in cancer risk and outcomes are associated with weight loss per se or are due to bariatric surgery-specific benefits, which are inherently challenging to delineate in patients ( Schauer et al, 2017 ; Alvarez et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who receive a VSG have a reduction of 57% excess weight after 2 years, which remains relatively stable out to 10 years post-surgery ( O’Brien et al, 2019 ). Remarkably, patients who undergo surgically induced weight loss have a reduction in all-cause mortality up to 60% ( Syn et al, 2021 ; Doumouras et al, 2020 ; Aminian et al, 2022 ). Despite promising benefits of weight loss, weight loss regimens are not yet widely adopted in cancer prevention, survivorship, or therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable evidence from retrospective and prospective cohort studies supports a decreased risk of endometrial cancer in patients with obesity who undergo bariatric surgery compared with nonsurgical matched controls ( 52 , 53 , 67 , 70 72 ). A prospective pilot study of the effects of bariatric surgery on the risk of endometrial pathology in women undergoing laparoscopic RYGB identified a 6.8% preoperative prevalence of occult hyperplastic endometrium, considered a precursor lesion for endometrial cancer, upon biopsy.…”
Section: Metabolic Surgery and Cancermentioning
confidence: 99%
“…Bariatric surgery achieves significant and long term weight loss and appears to be effective in reducing the risks of certain cancers. In the recently published SPLEN-DID (Surgical Procedures and Long-term Effectiveness in Neoplastic Disease Incidence and Death) cohort study, greater weight loss from bariatric surgery reduced obesity-associated cancer incidence in a dose-dependent manner [10]. However, from a global perspective, access to bariatric surgery is limited to a small fraction of the population, therefore may not be a feasible strategy to greatly reduce obesity-associated cancers worldwide.…”
mentioning
confidence: 99%